IDENTIFIKASI DISTRIBUSI POLA CURAH HUJAN DAN NERACA AIR KOTA DENPASAR - -, Daryono (Bumi Lestari; Vol 6 No 1, 2012)
Identification on rainfall pattern and water balance is very important for environtment research, water resources development and agricultural planning. This study used statistical and Thornthwaite and Mather (1957) method to analyse the water balance. The results show that wet season at Denpasar take place on November up to April and dry season take place on May up to October in every years. Water surplus period at Denpasar take place for 4 months (January- April) in amount 496 mm. Water deficit period take place for 6 months (May-October) in amount 298 mm.
Keywords: rainfall pattern, water balance, water surplus, water deficit